29th International Conference on Ocean, Offshore and Arctic Engineering: Volume 5, Parts a and B 2010
DOI: 10.1115/omae2010-20410
|View full text |Cite
|
Sign up to set email alerts
|

Feedback Analyses of Pipeline Embedment Over As-Laid Survey Results

Abstract: The as-laid embedment is a key parameter in the design of non-buried rigid pipelines. Large discrepancies are observed, for example in the number and length of predicted free spans, or in the global response to thermo-mechanical expansion, when this parameter is misevaluated. The employment of wide ranges to cover the uncertainties and ensure safety may hugely increase the project costs by mitigating what could not be an actual concern. Conversely, there is no reliable method to accurately predict this embedme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…As indicated, f dyn is essentially empirical, expressing the degree of agreement between a calculated embedment (based on a static analysis) and an observed value (influenced by dynamic effects). Reported f dyn values range from 1 to 8 (Lund, 2000;Bruton et al, 2006), which have been broadly confirmed for finegrained soils based on as-laid surveys from offshore Brazil, the North Sea, and offshore West Africa (Carneiro et al, 2010;Westgate et al, 2010aWestgate et al, , 2010b. The wide range of reported f dyn in fine-grained soils, together with the dearth of guidance in coarse-grained soils or carbonate soils, suggests that this approach could usefully be replaced with embedment prediction models that are more closely linked to (a) site-specific conditions, and (b) the underlying physical processes.…”
Section: Current State Of Practicementioning
confidence: 69%
“…As indicated, f dyn is essentially empirical, expressing the degree of agreement between a calculated embedment (based on a static analysis) and an observed value (influenced by dynamic effects). Reported f dyn values range from 1 to 8 (Lund, 2000;Bruton et al, 2006), which have been broadly confirmed for finegrained soils based on as-laid surveys from offshore Brazil, the North Sea, and offshore West Africa (Carneiro et al, 2010;Westgate et al, 2010aWestgate et al, , 2010b. The wide range of reported f dyn in fine-grained soils, together with the dearth of guidance in coarse-grained soils or carbonate soils, suggests that this approach could usefully be replaced with embedment prediction models that are more closely linked to (a) site-specific conditions, and (b) the underlying physical processes.…”
Section: Current State Of Practicementioning
confidence: 69%